Minimum Wage Effects on Employment, Substitution, and the Teenage Labor Supply: Evidence from Personnel Data - Giuliano, Laura (Journal of Labor Economics, 2013)
Using personnel data from a large US retail firm, I examine the firm’s response to the 1996 federal minimum wage increase. Compulsory increases in average wages had negative but statistically insignificant effects on overall employment. However, increases in the relative wages of teenagers led to significant increases in the relative employment of teenagers, especially younger and more affluent teenagers. Further analysis suggests a pattern consistent with noncompetitive models. Where the legislation affected mainly the wages of teenagers and so was only moderately binding, it led both to higher teenage labor market participation and to higher absolute employment of teenagers.